The potential of Waqf for maintenance and management of stratified properties in Malaysia - Mohamad, Nor Asiah; Sufian, Azlinor; Syed Abdul Kader, Sharifah Zubaidah (IIUM Press, International Islamic University Malaysia, 2017)
This article explores the possibility of implementing the concept of waqf within the financial management of a strata scheme for the purpose of covering the costs to maintain and manage common properties. High prices of land and the lack of strategic locations for housing has influenced developers to opt for stratified development. The challenge, most of the time, pertains to the maintenance of common areas, which requires substantial funds and professionalism, as well as skills in developing social and human relationships, despite the continual increase in the costs of management. Using doctrinal analysis of primary and secondary data, as well as comparative analysis with strata regulations in Australia, the study concludes that cash waqf can play a role as a potential vehicle to raise funds to maintain and manage common properties in strata schemes. The concept of waqf, where a certain category of properties is released from the ownership of man permanently while its benefits are dedicated to be used for the betterment of the public (ummah), is now regarded as a catalyst for the third sector economy. While religious reward may motivate Muslim owners or tenants to contribute to the waqf fund, other benefits offered such as financial security, sustainability, accountability and transparency would invite contribution and build trust from both, Muslims and non-Muslims. With adequate awareness, initiatives, and effective marketing of waqf products, the waqf concept would be able to provide a sustainable source of funds to cater to short term and long term maintenance plans for strata schemes.